2012
DOI: 10.1007/s12664-012-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic treatment of bleeding gastric varices with histoacryl (N-butyl-2-cyanoacrylate): a South European single center experience

Abstract: Background Endoscopic injection of N-butyl-2-cyanoacrylate is the current recommended treatment for gastric variceal bleeding. Despite the extensive worldwide use, there are still differences related to the technique, safety, and long term-results. We retrospectively evaluated the efficacy and safety of cyanoacrylate in patients with gastric variceal bleeding. Patients and Methods Between January 1998 and January 2010, 97 patients with gastric variceal bleeding underwent endoscopic treatment with a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Our study reinforces this claim, with a success rate of a single session of around 86%, which is comparable with 88-100% reported in the literature [2,4,14-20]. However, rebleeding rates have been reported to be between 16 and 35% in different studies [14][15][16][17][18][19][20]. To the best of our knowledge, this is the first study in which the outcomes following gastric variceal bleeding have been defined according to the Baveno V classification.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study reinforces this claim, with a success rate of a single session of around 86%, which is comparable with 88-100% reported in the literature [2,4,14-20]. However, rebleeding rates have been reported to be between 16 and 35% in different studies [14][15][16][17][18][19][20]. To the best of our knowledge, this is the first study in which the outcomes following gastric variceal bleeding have been defined according to the Baveno V classification.…”
Section: Discussionsupporting
confidence: 90%
“…Rajoriya et al [15] reported a rebleeding rate of 16%, whereas in a study by Kang et al [20] 24% of the patients had rebleeding over a mean follow-up of B1 year, which is comparable with our study. The most common etiology of cirrhosis was chronic hepatitis C in our study, which is different from the western countries, where alcoholic cirrhosis is the major culprit [17,19]. However, the outcomes after histoacryl therapy have been similar in both parts of the world.…”
Section: Discussionmentioning
confidence: 59%
“…Some studies have shown that the Child-Pugh score and associated HCC are risk factors for bleeding-related death [6,22,23], while another study reported that MELD score is a risk factor [24,25]; our study showed these relationships only on univariate analysis.…”
Section: Discussionmentioning
confidence: 46%
“…Th e fi ndings of our single-center retrospective study confi rm results reported by Rengstorff et al ( 6 ) and Monsanto et al ( 7 ), where the use of cyanoacrylate injection is very eff ective in controlling gastric variceal bleeding with an acceptable safety profi le. Studies from China, Portugal, and the United States have reported rebleeding rates in the range of 4% to 14.4% (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%